Ways of Forming Household Vocabulary of The Khalkha-Mongolian, Buryat And Kalmyk Languages - Trofimova, S. M.; Dzhambinova, N. S.; Kichikova, N. A.; Mandzhieva, E. B.; Balzhinimaeva, B. D. (Opción, 2019)
The article concerns the lexical-semantic subgroups of household vocabulary in the Khalkha-Mongolian, Buryat and Kalmyk languages, which are represented by monosyllabic, disyllabic and multisyllabic lexemes. In addition, the authors emphasize that the primary method of forming household vocabulary is correlative words that nominate new objects of reality, thereby enrich the vocabulary of Mongolian languages with new lexemes.